نموذجا- Nestlé ثنائية الذكاء الاقتصادي- خلق القيمة المشتركة في ظل جائحة كورونا- شركة: Duality of economic intelligence - creating shared value in light of the Corona pandemic - Nestlé company as a model - أحمد بن يوسف; فاطمة بلقواسمي (Journal of North African Economies, 2025)
The study aims to demonstrate how Nestlé's commitment to shared value steered economic intelligence practices during the coronavirus period; The descriptive analytical approach was used to analyze Nestlé's business during this period. The study concluded that nestlé’s shared value creation strategy contributed to activating economic intelligence in light of the pandemic, as its business translated the company’s acumen and intelligence in addressing external environmental threats while maintaining the strategy path, and based on these results, some recommendations were made, most notably the keenness to diagnose businesses from various aspects, so that decision-makers can formulate plans in proportion to what is imposed by reality.